Automation of the air conditioning system for aseptic rooms of pharmaceutical production - José Ricardo Nuñez Alvarez; Raidel Fidel Linares Vicente; Yelena Pérez Zamora; Eliana Noriega Angarita; Rodrigo Isacc Fonnegra Rodríguez; José Javier Lozano Mendoza (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
As modern control systems are becoming more complex, and the implemented technology more sophisticated, the importance of the different characteristics of those systems, such as reliability, availability, security, and protection, is increasing. In this article, an automation design for the air conditioning system of classified areas of the Parenteral solutions plant of the eastern pharmaceutical laboratory company of Santiago de Cuba province, Cuba, is proposed because there is a lack of optimal environmental conditions for development and production of pharmaceuticals at a large scale. The proposal is focused on the design of a supervision system and automatic control of the environmental variables that influence the drug production process. The entire algorithm for the design was developed to monitor critical and non-critical variables and control values of temperature, relative humidity, differential pressure, and air velocity according to standards established by pharmaceutical companies. The design of the automation system includes, apart from the control and supervision algorithm for operation efficiency, the necessary instrumentation.